Preparation and evaluation of the clinical efficacy and safety of tomato lotion containing lycopene - Shahtalebi Mohammad-Ali; Siadat Amir-Hosein; Karbasizade Setare (Shahrekord University of Medical Sciences, 2015)
Introduction: Skin aging starts at around age of 30 with wrinkling and pigmentations as its mainindicators. Delay and prevention of aging is a major concern for a great number of people. Thepurpose of this research was to develop and evaluate the efficacy of an anti-wrinkle tomato lotion,consisting of 5% w/w tomato powder in an oil-in-water (O/W) emulsion.Methods: Different O/W emulsions were prepared and stability tests were done on them. Theformulation that successfully passed the stability tests, was chosen and the Solanum lycopersicumpowder was added to the oily phase of this O/W emulsion. The prepared lotion was evaluated forpharmaceutical tests. In vitro permeation studies were performed to measure permeation throughcellulose acetate membrane by diffusion cell at sink condition. In vivo trial for examination of theanti-wrinkle efficacy of lotion was done on 10 healthy women as case group compared with 10volunteers using the placebo lotion (lotion base without Solanum lycopersicum powder) as controlgroup.Results: According to the experimented results on the formulated lotion, the efficient time durationfor lotion effectiveness was 42 days. Tomato powder formulated in base of lotion significantlydecreased wrinkles. Our formulation was compatible with skin and caused no sensitivity reactionin human modelsConclusion: The Lycopene in Solanum lycopersicum in this formulation has anti-aging effect. Thisformulation might be a strong candidate for treatment of skin wrinkles.